Analisis Efektivitas Audit Kepatuhan Dalam Mitigasi Resiko Fraud di Era Digital (Studi Kasus Pada PT. Bank Sumut Syariah KCP Hamparan Perak) - Putri, Laila Ramadani; Liswanty, Ina; Masyitah, Emi (ProBisnis : Jurnal Manajemen, 2025)
This research identified key issues through preliminary compliance audit findings, highlighting significant gaps between policy and practice. These findings underscore the critical role of compliance audits in identifying and addressing gaps in anti-fraud strategies. This research employed a qualitative approach with a case study design, focusing on PT. Bank Sumut Syariah KCP Hamparan Perak as a representative operational unit facing digitalization challenges and fraud risks. Data collection involved interviews with branch management and customer service, as well as document analysis. The analysis aimed to provide in-depth insights into how compliance audit procedures were adapted and implemented, the challenges faced by auditors and operational management, and the effectiveness of anti-fraud strategies in responding to audit findings. This research contributes to the literature on digital-era compliance auditing in Islamic banking and offers practical recommendations to strengthen fraud mitigation efforts.